Efektivitas Perendaman Larutan Nanas Queen Victoria sebagai Pereduksi Logam Fe pada Kerang Hijau (Perna viridis) - Widiyanto, Holisha; Julianti, Julianti; Sriwijayanti, Sriwijayanti; Sari, Puspita; Situmeang, Boima; Susvira, Dian (Jurnal Beta Kimia, 2024)
Excessive Fe heavy metal contamination cause health problems for humans. One of the marine biota that is susceptible to heavy metal contamination is green mussels. Green mussels (Perna viridis) are a food that is very often consumed by humans. This Fe metal which derived with materials that are chelating agents such as citric acid, one of the fruits that contain citric acid is the Queen Victoria pineapple. The research aims to determine the effectiveness of soaking Queen Victoria pineapple solution in reduces Fe metal in green mussels. The pineapple solution immersion test was carried out with varying concentrations of 25, 50 and 75% with soaking times of 15, 30 and 45 minutes which were analyzed using inductively coupled plasma (ICP). The highest reduction results were at a concentration of 25% with a soaking time of 30 minutes, amounting to 60.58%.